In vitro study of Nigella sativa and thymoquinone activity on endothelial activation and monocyte adhesion - Yuhainis Firus Khan, Al'Aina; Mohtar, Fahmi; Rahman, Thuhairah Abdul; Muid, Suhaila Abdul; Froemming, Gabriele Ruth Anisah; Nawawi, Hapizah (Journal of Applied Biomedicine, 2023)
INTRODUCTION: Thymoquinone (TQ) is one of the bioactive compounds in Nigella sativa (NS). Also known as black seeds/cumin, it has been postulated to possess anti-atherogenic properties. However, research on the effects of NS oil (NSO) and TQ on atherogenesis remain scarce. The aim of this study is to determine gene and protein expression of Intercellular Adhesion Molecule-1 (ICAM-1), Vascular Cell Adhesion Molecule-1 (VCAM-1), and Endothelial-eukocyte adhesion molecule (E-selectin) in Human Coronary Artery Endothelial Cells (HCAECs). METHODS: HCAECs were stimulated for 24 hours (h) with 200 μg/ml of Lipopolysaccharides (LPS) and different concentrations of NSO (55, 110, 220, 440 μg/ml) or TQ (4.5, 9.0, 18.0, 36.0 μm). The effects of NSO and TQ on gene and protein expressions were measured using multiplex gene assay and ELISA assay, respectively. Rose Bengal assay was used to analyse monocyte binding activity. RESULTS: NSO and TQ significantly reduced ICAM-1 and VCAM-1 gene and protein expressions. TQ showed significant reduction activity of the biomarkers in dose dependent manner. HCAECs pre-treated with NSO and TQ for 24 h significantly lowered monocytes adherence compared to non-treated HCAECs. CONCLUSIONS: NSO and TQ supplementation have anti-atherogenic properties and inhibit monocytes' adherence to HCAECs via down-regulation of ICAM-1 expression. NSO could potentially be incorporated in standard treatment regimens to prevent atherosclerosis and its related complications.
Keywords: endoteliální buňky; Monocytes; cévní buněčněadhezivní molekula-1; monocyty; Intercellular Adhesion Molecule-1; Humans; Endothelial Cells; mezibuněčná adhezivní molekula-1; Vascular Cell Adhesion Molecule-1; lidé; Nigella sativa